Dificuldades enfrentadas por alunos do ensino médio no aprendizado da matemática. - SILVA, Jefferson Pedro Silva e (2025)
This is research with a quantitative and qualitative with exploratory and descriptive purposes and field research procedures, using discursive textual analysis in the analysis and interpretation of data and had as generais objective is to identify the causes of the difficulties faced by high school students in understanding mathematical teaching. Fifty high school students from Escola Maestro Waldemar Henrique, located in the neighborhood of Benguí in Belém do Pará, participated in this study. For data collection, a questionnaire and interviews were carried out together with the students. The difficulties studied in this research were lack of interest, lack of motivation from parents or guardians, finding mathematics difficult and distraction in the classroom. And in the analysis of the questionnaire and during the interviews it was observed that the four difficulties studied in this work were pointed out by the students, where there was a greater number of students indicating that finding mathematics difficult and distraction in the classroom are the difficulties that most affect the understanding of mathematical teaching during classes. And using the theoretical framework of this work, we can indicate as a proposal the application of mathematical games during classes, in addition to presenting to students the applications that the subjects studied in the classroom have in their daily lives, also showing the fundamental importance that These themes have for the sciences, in their different levels of application.